2001
DOI: 10.1101/gad.873901
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the transcriptional machinery through GAL11P: structure and interactions of the GAL4 dimerization domain

Abstract: The GAL4 dimerization domain (GAL4-dd) is a powerful transcriptional activator when tethered to DNA in a cell bearing a mutant of the GAL11 protein, named GAL11P. GAL11P (like GAL11) is a component of the RNA-polymerase II holoenzyme. Nuclear magnetic resonance (NMR) studies of GAL4-dd revealed an elongated dimer structure with C 2 symmetry containing three helices that mediate dimerization via coiled-coil contacts. The two loops between the three coiled coils form mobile bulges causing a variation of twist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 55 publications
5
40
0
2
Order By: Relevance
“…Taken together, the artificial recruitment studies show that, under some circumstances, transcription can be enhanced by direct recruitment of the transcription machinery, but do not by themselves prove that natural activators work by recruitment. Similar conclusions were reached in a genetic study where a mutation (Gal11p) in the Mediator subunit Gal11/ Med15 was found that created a new protein-protein interaction with the Gal4 dimerization domain and stimulated transcription in the absence of a Gal4 activation domain (Barberis et al 1995;Hidalgo et al 2001).…”
Section: Activation By Recruitmentsupporting
confidence: 62%
“…Taken together, the artificial recruitment studies show that, under some circumstances, transcription can be enhanced by direct recruitment of the transcription machinery, but do not by themselves prove that natural activators work by recruitment. Similar conclusions were reached in a genetic study where a mutation (Gal11p) in the Mediator subunit Gal11/ Med15 was found that created a new protein-protein interaction with the Gal4 dimerization domain and stimulated transcription in the absence of a Gal4 activation domain (Barberis et al 1995;Hidalgo et al 2001).…”
Section: Activation By Recruitmentsupporting
confidence: 62%
“…Both binding and activation are only seen in cells bearing the Gal11P mutation and not in cells with normal Gal11 protein. Ala scanning mutagenesis over the entire 50-97 regions revealed that predominantly hydrophobic residues (L69, L70, I71, F72, L86, L89, L92, L93, L96, and F97) were important for both transcriptional activation and Gal11P binding (34). It is very unlikely that so many hydrophobic residues could be part of a binding site, and we suggest instead that these residues are buried in intact Gal4.…”
Section: Construction Of Minigal4mentioning
confidence: 93%
“…The maximum number of Ts mutants was obtained at position 68. While this work was in progress, the NMR structure of the isolated Gal4 dimerization domain (residues 50-106) was reported (34). NMR spectra as a function of pH and temperature revealed the presence of several temperature-dependent, noncooperative changes, indicating a flexible and dynamic structure.…”
Section: Construction Of Minigal4mentioning
confidence: 99%
“…The resulting complex is quite stable (K d Յ 3 ϫ 10 Ϫ7 M) under representative in vitro conditions (50). As summarized in Fig.…”
Section: Yeast Tbp Amino-terminal Domains Interact In Living Ementioning
confidence: 67%